Composite Hydrogel of Methacrylated Hyaluronic Acid and Fragmented Polycaprolactone Nanofiber for Osteogenic Differentiation of Adipose-Derived Stem Cells - Madhumita Patel; Won-Gun Koh (MDPI AG, 2020)
Composite hydrogels with electrospun nanofibers (NFs) have recently been used to mimic the native extracellular matrix. In this study, composite hydrogels of methacrylated hyaluronic acid containing fragmented polycaprolactone NFs were used for bone tissue engineering. The composite (NF/hydrogel) was crosslinked under ultraviolet (UV) light. The incorporation of fragmented polycaprolactone NFs increased the compression modulus from 1762.5 to 3122.5 Pa. Subsequently, adipose-derived stem cells incorporated into the composite hydrogel exhibited a more stretched and elongated morphology and osteogenic differentiation in the absence of external factors. The mRNA expressions of osteogenic biomarkers, including collagen 1 (Col1), alkaline phosphatase, and runt-related transcription factor 2, were 3-5-fold higher in the composite hydrogel than in the hydrogel alone. In addition, results of the protein expression of Col1 and alizarin red staining confirmed osteogenic differentiation. These findings suggest that our composite hydrogel provides a suitable microenvironment for bone tissue engineering.